1998
DOI: 10.1677/joe.0.1590349
|View full text |Cite
|
Sign up to set email alerts
|

UCP2, UCP3 and leptin gene expression: modulation by food restriction and leptin

Abstract: To determine the effects of food restriction and leptin administration on several transcripts involved in energy homeostasis, we examined leptin, uncoupling proteins (UCP) 1, 2 and 3, lipoprotein lipase (LPL), 3 -adrenergic receptors ( 3 AR) and hormone-sensitive lipase (HSL) mRNA levels in brown adipose tissue (BAT) and epididymal (EWAT) and perirenal (PWAT) white adipose tissue in three groups of rats. The groups were administered leptin for 1 week, or had food restricted to the amount of food consumed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
3
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 41 publications
(50 reference statements)
11
43
3
1
Order By: Relevance
“…Thus, in this dietary trial, high-energy diet intake significantly increased iBAT UCP1 and UCP3 mRNA levels as previously reported [11,30], which suggests that mechanisms controlling UCP1 and UCP3 expression may be similar. Also, several studies carried out to clarify UCP regulation under different experimental circumstances revealed that ␤ 3 -adrenergic agonists [10,31], leptin infusion [32,33], thyroid hormone administration [4,11] and cold exposure [11,32] induced a significant increase in UCP1 and UCP3 mRNA levels. The results of these studies suggested that the gene expression of both UCPs were similarly modified by those factors that occur after feeding a high-energy diet.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this dietary trial, high-energy diet intake significantly increased iBAT UCP1 and UCP3 mRNA levels as previously reported [11,30], which suggests that mechanisms controlling UCP1 and UCP3 expression may be similar. Also, several studies carried out to clarify UCP regulation under different experimental circumstances revealed that ␤ 3 -adrenergic agonists [10,31], leptin infusion [32,33], thyroid hormone administration [4,11] and cold exposure [11,32] induced a significant increase in UCP1 and UCP3 mRNA levels. The results of these studies suggested that the gene expression of both UCPs were similarly modified by those factors that occur after feeding a high-energy diet.…”
Section: Discussionmentioning
confidence: 99%
“…In the inguinal fat pad of ob/ob mice, treatment with leptin induces the expression of Ucp2 and other genes involved in lipid metabolism, including SREBPs and PPARs (84). In rat studies, subcutaneous administration of leptin was found to induce up-regulation of Ucp2 in epididymal fat pads (85). Adenovirus-mediated overexpression of leptin can also induce up-regulation of Ucp2 in pancreatic beta-cells and subcutaneous white adipose tissues (86).…”
Section: Regulation By Hormonesmentioning
confidence: 99%
“…In addition, both fasting plasma leptin [72] and insulin concentrations [72,73] are negatively correlated with WAT UCP2 mRNA expression, although this finding is not supported by other data [65]. In wellcontrolled studies in rats, where leptin effects can be separated from those of weight loss, both intracerebroventricular [42] and peripherally-administered leptin [74] increase UCP2 expression in WAT. This effect is likely to be mediated by the sympathetic nervous system because leptin added directly to human adipocyte explants does not alter UCP2 expression [75].…”
Section: Fuel Metabolismmentioning
confidence: 85%
“…In addition to the complications arising from the dominance of UCP1 in adaptive thermogenesis, there is considerable variability in reported tissue UCP2 mRNA. Since leptin appears to upregulate UCP2 [42,74], it might be hypothesized that leptin-deficient or leptin-resistant animals would have attenuated UCP2 expression. However, not only is leptin not essential for UCP2 expression, it seems that even similar causes of obesity have disparate effects on UCP2 expression [9,16,89,144].…”
Section: Relation Of Ucp2 With Metabolic Diseasesmentioning
confidence: 99%